بناء مقياس عزوف الجمهور عن حضور مباريات الدوري وتقنينه لدى لاعبي كرة القدم في اقليم كوردستان/العراق للموسم الكوري (2022-2023) - حميد, أ.م.د. عماد صدرالدين (Sulaimani Journal for Humanities, 2023)
The research aims to: -Building a measure of the public's aversion to attending football matches on football players in the Kurdistan Region / Iraq. -Finding standard levels to measure the public's aversion to football matches on football players in the Kurdistan Region / Iraq. The research community was determined intentionally, and it consisted of the players of the Premier League and League One football clubs participating in the league 2022-2023 in the Kurdistan Region / Iraq, which numbered (180) players as a sample for construction and standardization, and they were randomly selected from the research community, while the sample of the scale application was (120) players. They were selected from the research community, Where their number reached (120) players, which consisted of players from clubs such as (Hawler, Shaqlawa, Braiti, Hendrin, Peshmerga, Ararat, Sanaa, Jihan, Brusk), and some of the players were excluded due to not responding to the questionnaire, absence in training due to injury, or due to the lack of knowledge of the language for some foreign players, Also (20) players were excluded from the Koya football club because of their participation in the exploratory experiment and extracting the stability of the scale. Thus, the final sample size reached 120 players out of 180 players, at a rate of 66.6%. The researcher used the descriptive approach in two ways: survey and correlation, and after obtaining the results, they were discussed in a scientific manner supported by the sources to achieve the objectives of the research. In light of the research results, the researcher reached the following conclusions: - Relying on the current scale of football federations and stakeholders -Conducting a similar study dealing with the reasons for the reluctance of the sports fans to attend matches in the women's games. - Use the scale reached by the researcher on players of age groups and national teams. - Conducting similar studies dealing with the reasons for the reluctance of sports fans in individual and team games. - Urging the media not to charge negative media to the masses because of the competition, which is reflected in the lack of public attendance at the stadiums. - Holding cultural programs and seminars that bring together journalists, officials and sports fans. - The need to focus on awareness and guidance by the stakeholders and the media to the sports audience in order to raise awareness and develop sports culture.